Investigation of Postgraduate Randomized Controlled Nursing Theses on Menopause Period: A Systematic Review - Selin Ahsun; Figen Kazankaya; Gül Ertem (Global Nursing Insights, 2026)
Aim: Menopause is a critical period affecting women’s health and quality of life, and nursing interventions play a key role in managing this transition. This study aimed to review randomized controlled postgraduate nursing theses on menopause in Turkey.Material and Methods: The YÖKTEZ database was searched using the keywords "menopause", "randomized", and "nursing". Two independent researchers conducted the search, and 27 theses were identified. After applying the inclusion criteria—randomized controlled design, focus on menopause, nursing field, and open full-text access—21 theses were analyzed using thematic and quantitative content analysis. Of the included theses, four were master's and 17 were doctoral. Results: Of the 21 theses included, 63.6% were conducted in nursing departments and 36.4% in women’s health and diseases nursing. The theses were conducted between 2009 and 2024, with 77.2% completed within the last five years. Most interventions targeted postmenopausal women (59%), followed by women during menopause (27%) and premenopause (14%). Interventions were classified as nursing theory-based approaches (31.8%), complementary and alternative medicine practices (31.8%), and education/counseling programs (36.4%). The most frequently evaluated outcomes were quality of life (63.6%) and vasomotor symptoms (54.5%), with significant improvements reported in all studies assessing these outcomes. Positive effects were also observed in sexual health, sleep quality, psychological well-being, health literacy, osteoporosis awareness, and exercise behaviors. Conclusions: All reviewed postgraduate nursing theses from Turkey indicated that the interventions applied led to reduced menopausal symptoms and improved quality of life. It is recommended that nurses incorporate evidence-based interventions highlighted in these theses into their clinical practice. Implication for nursing practice: These results highlight that nursing management and education programs should prioritize theory-driven, evidence-based interventions to improve menopausal women’s adaptation and well-being.